2018
DOI: 10.1002/cbin.10937
|View full text |Cite
|
Sign up to set email alerts
|

Glycine improves the remodeling process of tenocytes in vitro

Abstract: Tendinitis changes the biochemical and morphological properties of the tendon, promoting an increase of activity of metalloproteinases and disorganization of collagen bundles. Tenocytes, the primary cells in tendon, are scattered throughout the collagenic fibers, and are responsible of tendon remodeling and tissue repair in pathological condition. In vivo, glycine, component of the typical Gly-X-Y collagen tripeptide, showed beneficial effects in biochemical and biomechanical properties of Achilles tendon with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The participants were able to return to running after the treatment but did not reach preinjury levels within the duration of the study. The COL used contained 22% glycine, which is known to enhance collagen matrix organisation strength, reduce inflammation and influence tenocyte metabolism in tendons (Vieira et al 2018). The eccentric training protocol used may have also improved the tendon structure and reduced neovascularization (associated with tendinosis; Ohberg and Alfredson 2004).…”
Section: Effects Of Collagen Supplementation On Joint Function and Recovery From Joint Injuriesmentioning
confidence: 99%
“…The participants were able to return to running after the treatment but did not reach preinjury levels within the duration of the study. The COL used contained 22% glycine, which is known to enhance collagen matrix organisation strength, reduce inflammation and influence tenocyte metabolism in tendons (Vieira et al 2018). The eccentric training protocol used may have also improved the tendon structure and reduced neovascularization (associated with tendinosis; Ohberg and Alfredson 2004).…”
Section: Effects Of Collagen Supplementation On Joint Function and Recovery From Joint Injuriesmentioning
confidence: 99%
“…These clinical findings extend on two earlier studies [32,33], that reported respectively a pain modulating and in vitro anti-inflammatory effect of a nutraceutical containing collagen, mucopolysaccharides and vitamin C. Furthermore, in a rodent model of collagenase-induced Achilles tendinopathy, a 5% glycine-rich diet for 3 weeks improved hydroxyproline, glyosaminoglycans and non-collagenous protein content of the Achilles tendon [12]. Glycine has also been shown to improve collagen matrix organisation strength and tenocyte remodelling, most likely by modulating both TNF-alpha, matrix metalloproteases and the availability of collagen precursors [14]. As the sCP supplement in the present study contains 22% of glycine [11], it could be postulated that the increased intake of 1.1 g of glycine per day may have contributed to observed clinical improvements in VISA-A scores during sCP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical studies are still scarce, a recent International Olympic Committee (IOC) consensus statement on dietary supplements in high-performance athletes [6] proposes that dietary supplementation containing gelatin or hydrolysed collagen could potentially be useful for athletic populations as increased intake of collagen-derived peptides has been shown to modulate collagen synthesis [7] and reduce tendon- [8] and joint-related pain [9,10]. Others have shown that glycine, as the most abundant component of collagen hydrolysates [11], has disease-modifying properties in both animal [12,13] and in vitro [14] models of tendinopathy. There is also first evidence, that collagen peptides might improve functional ankle properties in chronic ankle instability [15].…”
Section: Introductionmentioning
confidence: 99%
“…Tenocytes are highly specialized mesenchyme-derived cells with important roles in synthesizing ECM and maintaining tendon structures in vivo (23). Cao et al constructed tissueengineered artificial tendons for the first time (24), but they also indicated that tenocytes are relatively difficult to grow and expand in vitro.…”
Section: Tenocytesmentioning
confidence: 99%
“…Thus, many researchers have explored the strategies to promote proliferation and at the same time, support a stable phenotype of tenocytes. At present, it has been reported that thyroid hormone T3, transforming growth factor (TGF)-b1, glycine, platelet-rich plasma, and insulinlike growth factor 1 could enhance the proliferation and differentiation capacity of tenocytes, as well as stimulate the secretion of ECM (23,(26)(27)(28)(29). Mechanical force can also regulate tenocyte differentiation (30).…”
Section: Tenocytesmentioning
confidence: 99%